Penerapan Metode Example Nonexample dalam Pembelajaran Bahasa Indonesia Kelas C Program Studi S1 Keperawatan di STIKes Bina Sehat PPNI Mojokerto - moh. zainudin zain; Raras Merbawani; Asef Wildan Munfadlila (Medan Resource Center, 2022)
Abstract This Research described the application of the example non example method in learning Indonesian in class C of the S-1 Nursing Science Study Program at STIKes Bina Sehat PPNI Mojokerto. The material for preparing reports on community service activities was a series of language learning materials that had been prepared by the lecturer in the semester learning plan. In learning activities, students were required to always be active and creative. In addition, the role of the lecturer as one of the components of learning becomed very important and must be able to apply and develop learning methods appropriately. Through the example non example method, students can be directly and actively involved and can think critically in the learning process, thus making the learning atmosphere more fun and meaningful. This research used a type of field research (field research) with a qualitative approach. Data collection techniques included observation and documentation. The data analysis carried out by the researcher was as follows: (1) data reduction. This activity includes selecting data on the basis of its level of relevance and relation to data groups, compiling data in similar units, and creating codes. (2) displaying data by compiling relevant data, (3) drawing conclusions to get a meaning of scattered symptoms to have deep meaning. Based on the results and discussion, it can be concluded that the implementation of the example non example method has been going well. students can compile reports on the results of community service activities more regularly and systematically. Keywords: learning Indonesian, compiling reports, method example non example